Cost Oriented (humanoid) robots. Issue 24 (2015) - Bauer, J.; Kopacek, P.; dÀpolito, F.; Kräuter, L.; Dorna, I.
Abstract: Cost oriented (humanoid) robots - CO(H)R - were introduced in 2011. These robots will be able to support humans in everyday life like on the working place, in the household, in leisure and entertainment, and should be available on the market for a reasonable price. Based on previous works in this paper a new control concept and a new "CO gear" will be presented. If we will have in the future CO(H)R the old dream of the robotics community "personal" robots is realized. In each home there will be at least one. Finally open questions like "human - robot" interaction, robo-ethics, …. will be shortly outlined.